Metal enhanced luminescence of cerium oxide (IV) hollow sub-microspheres with au, aupd and pd nanoparticles - Guzmán, Mario; Chávez García, Dalia H.; Nieto Sánchez, Amanda G.; Juárez, Karla O.; Simakov, Andrey (My University, 2021)
This work reports an analysis of the luminescent properties of Cerium oxide (IV) hollow sub-microspheres (CeO2-HS) as well as the effect of the presence of Au, AuPd and Pd NPs over the mentioned properties. CeO2-HS were synthesized via hydrothermal method, then the CeO2-HS were impregnated with the metal precursors and by a reduction process the metal nanoparticles (NPs) were obtained. CeO2-HS were characterized by XRD, Raman, UVVis and TEM. The CeO2-HS with metal NPs deposited on them were analyzed using UV-Vis and TEM. All samples luminescent excitation and emission spectra were recorded. It was observed that the presence of metal NPs dramatically increases the emission intensity compared to the CeO2-HS without metal NPs. Finally, it was also observed a clear slight but evident displacement of the main emission peak between samples with and without metal NPs
Keywords: Ceria; Hollow spheres; Metal enhanced luminescence; Noble metal NPs; Campus Ensenada